Deformation in Jurassic-Cretaceous Redbeds from Champasak and Khammouane, Lao PDR, Revealed by Anisotropy of Magnetic Susceptibility - Sounthone Singsoupho (Science Faculty of Chiang Mai University, 2019)
The anisotropy of magnetic susceptibility measurement technique was applied to the Jurassic-Cretaceous redbeds in the Champasak and Khammouane provinces of the southern and central part of Lao PDR, in order to define the correlation between the magnetic anisotropic data and degree of deformation in redbeds due to tectonic stress field focusing on the mountain belt and fault areas. The results show that the alignment of Kmax axes is predominantly parallel to the trending of the mountain belts (or fold axis) and the strike of faults. The orientation patterns of the principal axes of the susceptibility ellipsoid did not show the typical pattern usually found in undeformed sedimentary rocks. It can be concluded that the development of the triaxial and pencil structure patterns of secondary magnetic fabric correlates well with the degree of rock deformation which is caused by tectonic compression acting on the rocks.